Combustion Behavior of Sewage Sludge Hydrochar Obtained in Fast Hydrothermal Carbonization - de Campos Avanzi, Guilherme Afonso; Santos, Vinicius Sarracini [UNESP]; Constantino, Isabela Carreira [UNESP]; Metzker, Gustavo [UNESP]; Boscolo, Mauricio [UNESP]; Bisinoti, Márcia Cristina [UNESP]; Ferreira, Odair Pastor; Moreira, Altair Benedito [UNESP] (American Chemical Society (ACS), 2025)
Sewage sludge (SS) is a complex biomass with a high content of inorganic and organic matter. The hydrothermal carbonization process (HTC) was used to produce a carbonaceous material with energy densification derived from SS. For this, temperatures of 200, 240, and 280 °C, reaction times of 30, 75, and 120 min, without or with H2SO4 acid addition (0.5 and 1% v/v) were assessed in the SS HTC process. Hydrochars (HC) were characterized by FTIR spectroscopy and CHNS elemental and thermogravimetric analyses. The energetic evaluation was performed by a higher heating value (HHV) estimation. HC presented yields ranging from 44.4 to 57.8% with a high content of organic matter and ashes due to the composition of SS. The H/C and O/C atomic ratios, ranging from 0.93 to 1.93 and 0.12 to 0.39, respectively, indicated the carbonization of SS due to dehydration and decarboxylation reactions, resulting in a carbonaceous material. FTIR analysis indicates the presence of different organic groups (i.e., O-H, C-H, CC, and CO), as well as inorganic ones (Si-O). HHV of HC ranged from 13.4 to 16.5 MJ kg-1 with energy densification from 0.9 to 1.1, indicating a similar energy content of HC and SS. However, energy yield efficiency ranged from 38.2 to 57.2%, being correlated with temperature and time in both acidic conditions. Combustion behavior of HC indicates that higher thermal stabilization was provided with the increase of temperature, time, and sulfuric acid.